2012
DOI: 10.1007/s11420-012-9279-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor Analysis for 30-Day Mortality after Primary THA in a Single Institution

Abstract: The purpose of this study was to determine the prevalence of, and associated risk factors for, 30-day perioperative death following primary total hip arthroplasty (THA). Data of all the patients were compiled from the computerized total joint registry at a single institution. Between May 1993 and May 2006, 3,232 consecutive primary THA (2,453 elective and 779 nonelective) were performed. Eleven deaths occurred during the first month after surgery (0.34 %). Thirty-day mortality rate after elective THA was 0.08 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The studies in this review found that an American Society of Anaesthesiologists risk score > 3, 6 , 8 , 14 Charlson co-morbidity index > 3, 8 , 12 , 16 , 21 , 35 use of general anaesthesia, 2 , 8 and prior cardiovascular disease, 9 , 12 , 14 , 16 were risk factors for mortality. Comba et al 14 report that cardiovascular disease increased the risk of mortality eight-fold (odds ratio 8.83; 95% CI 1.78 to 43.6). Studies looking at earlier, peri-operative mortality, have identified pre-existing cardiovascular disease as a strong risk factor for early mortality after THR.…”
Section: What Are the Risk Factors For Mortality?mentioning
confidence: 75%
See 2 more Smart Citations
“…The studies in this review found that an American Society of Anaesthesiologists risk score > 3, 6 , 8 , 14 Charlson co-morbidity index > 3, 8 , 12 , 16 , 21 , 35 use of general anaesthesia, 2 , 8 and prior cardiovascular disease, 9 , 12 , 14 , 16 were risk factors for mortality. Comba et al 14 report that cardiovascular disease increased the risk of mortality eight-fold (odds ratio 8.83; 95% CI 1.78 to 43.6). Studies looking at earlier, peri-operative mortality, have identified pre-existing cardiovascular disease as a strong risk factor for early mortality after THR.…”
Section: What Are the Risk Factors For Mortality?mentioning
confidence: 75%
“…Of the deaths that occurred in this series, ischaemic heart disease accounted for the majority (41.1%), followed by cerebrovascular accidents (23.1%), and pulmonary embolism (11.8%). 49 Of the nine studies in this review reporting cause of mortality, eight identified cardiovascular causes (generally myocardial infarction or heart failure) as the leading cause of death, 7 - 9 , 12 , 14 , 16 , 18 , 28 and in one small study, cerebrovascular accident was the leading cause of death. 33 Cardiovascular disease is repeatedly cited as the leading cause of death following THR in modern series, followed by cerebrovascular disease or fatal pulmonary embolus.…”
Section: What Are the Common Causes Of Mortality?mentioning
confidence: 99%
See 1 more Smart Citation
“…The 90-day mortality risk following hip and knee arthroplasty is reported to be 0.2% to 0.3%, only one third of which is attributed to VTE. 49,50 Furthermore, observational data indicate that surgery factors can also impact on mortality risk following hip and knee arthroplasty. For example, the risk of dying is significantly higher following hip arthroplasty compared to knee arthroplasty (3.0% vs. 0.1%).…”
Section: Mortalitymentioning
confidence: 99%
“…Neither the NHFS nor our modified score includes perioperative factors. Whilst these factors, such as pre-operative waiting time, type of femoral implant, prolonged operative time and perioperative anaemia [ 21 23 ], are known to influence post-operative outcomes, they are by definition not known at the point of admission to hospital. This is where risk scores such as the NHFS have most clinical utility in informing discussions with the patients regarding outcomes.…”
Section: Discussionmentioning
confidence: 99%